HUBUNGAN ANTARA EMOSI POSITIF YANG DIALAMI MAHASISWA DENGAN PRESTASI AKADEMIK PADA MAHASISWA FKIP UNILA TAHUN AKADEMIK 2011/2012 - Era Hidayah; Giyono Giyono; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of the research objective is the author wanted to determine therelationship between positive emotions that experienced by students with theacademic achievement of students FKIP Lampung University academic year2011/2012. The problem in this research is the low student academic achievement.The main problem in this research is